MENEPIS TRADISI CAROK MELALUI MODERASI BERAGAMA DI MADURA : Sohibuddin - Suadah, Muhammad shohibuddin; Humaidy, Mohammad Ali Al; Efendi, Agik Nur; Maimun, Maimun (DIALEKTIKA, 2024)
Carok is often used as a last resort by the Madurese people to resolve a problem due to their inherently tough nature. In this context, there is a demand for efforts to overcome this tradition. This research aims to implement the values of religious moderation to minimize the occurrence of the carok tradition in Madura. This study uses a library research method with primary data sources being the concept of religious moderation. Secondary data sources are obtained from literature such as books, journals, and relevant websites aligned with the research topic. The findings of this research are as follows: The carok tradition is a violent practice carried out by the Madurese as a form of defense concerning their self-esteem when their dignity is trampled, their wives are disturbed, and their families are harmed. There are three factors that lead the Madurese to carry out carok: when their dignity is trampled, their wives are disturbed, and their families are harmed. Religious moderation is a moderate Islamic concept that can counteract and minimize the occurrence of carok in Madura by instilling and applying socio-religious moderation values such as tolerance, engaging in deliberation to resolve conflicts, avoiding excessiveness, and being anti-violence.